Odhad složení komunálních odpadů z pohledu obalů - Doležalová, Adéla (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Předložená diplomová práce se zabývá odhadem zastoupení materiálově využitelných složek v komunálních odpadech se zaměřením na obaly. Odhad je proveden na základě analýzy finančního vydání za jednotlivé produkty s pomocí tzv. spotřebního koše. Součástí práce je také rešerše životního cyklu obalu a s ní spojená legislativa.

This master´s thesis focuses on prediction of presence of reusable material components in municipal waste with special focus on packaging materials. This prediction is based on analysis of financial costs of individual products according to the so-called market basket. Research of packaging´s life cycle and involving legislature is also a part of this thesis.
Estimation of municipal solid waste composition from the perspective of packaging
Keywords: Komunální odpad; analýza složení odpadů; odpad z obalů; obaly; Municipal waste; waste composition analysis; packaging waste; packaging